Characteristics and source-pathway of microplastics in freshwater system of China: A review. (June 2022) - Zhao, Mengjie; Cao, Yanxiao; Chen, Tiantian; Li, Honghu; Tong, Yifei; Fan, Wenbo; Xie, Yuwei; Tao, Ye; Zhou, Jingcheng
Abstract: China plays a key role in global plastic production, consumption and disposal, which arouses growing concern about microplastics (MPs) contamination in Chinese freshwater systems. However, few reviews have discussed the characteristics of MP pollution in whole freshwater systems at a national scale. In this review, we summarized the characteristics, sources and transport pathways of MPs in Chinese freshwater systems including surface water and sediment. Results showed that current research mainly focused on the middle and lower reaches of the Yangtze River and its tributaries, as well as lakes and reservoirs along the Yangtze River. Large-scale reservoirs, rivers and lakes located in densely populated areas usually showed higher abundances of MPs. The majority of MPs in Chinese surface water and sediment mainly consisted of polyethylene and polypropylene, and the most common morphologies were fibers and fragments. To identify the sources and pathways, we introduced the source-sink-pathway model, and found that sewage system, farmland and aquaculture area were the three most prevalent sinks in freshwater systems in China. The source-sink-pathway model will help to further identify the migration of MPs from sources to freshwater systems. Graphical abstract: Image 1 Highlights: MP abundance in surface water in China showed medium-high pollution level. MPs contents in Chinese sediments were comparable to those in other countries. The source–sink–pathway model of MPs in freshwater systems was constructed.